2019
DOI: 10.1038/s41598-019-53695-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the BAD pathway is a marker of triple-negative status and poor outcome

Abstract: Triple-negative breast cancer (TNBC) has few therapeutic targets, making nonspecific chemotherapy the main treatment. Therapies enhancing cancer cell sensitivity to cytotoxic agents could significantly improve patient outcomes. A BCL2-associated agonist of cell death (BAD) pathway gene expression signature (BPGES) was derived using principal component analysis (PCA) and evaluated for associations with the TNBC phenotype and clinical outcomes. Immunohistochemistry was used to determine the relative expression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Gene expression microarray datasets were obtained from the GEO database ( https://www.ncbi.nlm.nih.gov/geo/ ) according to the following requirements: (1) dataset was mRNA expression profile data; (2) the information of the platform annotation was accessible; (3) the expression data of microarray had been published. Therefore, the datasets including GSE115275 [ 33 ] and GSE62931 [ 34 ] were downloaded by GEO query package in R software (version 3.6.1, https://www.r-project.org ). Meanwhile, mRNA sequencing data of 1247 samples of breast cancer and normal breast tissue were acquired from the TCGA database ( http://portal.gdc.cancer.gov/ ).…”
Section: Methodsmentioning
confidence: 99%
“…Gene expression microarray datasets were obtained from the GEO database ( https://www.ncbi.nlm.nih.gov/geo/ ) according to the following requirements: (1) dataset was mRNA expression profile data; (2) the information of the platform annotation was accessible; (3) the expression data of microarray had been published. Therefore, the datasets including GSE115275 [ 33 ] and GSE62931 [ 34 ] were downloaded by GEO query package in R software (version 3.6.1, https://www.r-project.org ). Meanwhile, mRNA sequencing data of 1247 samples of breast cancer and normal breast tissue were acquired from the TCGA database ( http://portal.gdc.cancer.gov/ ).…”
Section: Methodsmentioning
confidence: 99%
“…We first characterized BAD protein and phosphoprotein levels during mammary gland development in the wild-type animal. Serines 112, 136, and 155 are coordinately phosphorylated 26 and we used either anti-PS112 or anti-PS136 antibodies that were validated for western blot or immunofluorescence, to monitor phosphorylated BAD (P-BAD). Total BAD protein levels are similar in pubertal, nulliparous adult and involuting glands and elevated in pregnant glands (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2h, i). Since in this TMA the overall survival data of the patients had been reported 29 , we stratified the patients based on the levels of TROLL-2 and TROLL-3 and found that high levels of either lncRNA correlated with reduced overall survival of these breast cancer patients ( Fig. 2c, d).…”
Section: Resultsmentioning
confidence: 99%
“…The Moffitt tissue microarrays (TMAs) used in this study consisted of: (i) 68 breast cancer samples comprising 43 triple negative and 25 non-triple negative breast cancers (TMA-5) 29 ; and (ii) 100 melanoma samples and 6 control cases (TMA-4). The formalin-fixed and paraffin-embedded biopsies were used to produce 0.6 mm cores, which were assembled into the two TMAs by the Tissue Core Facility at the H. Lee Moffitt Cancer Center & Research Institute under delegated ethical authority of the Moffitt Research Ethics Committee with written informed consent from contributing patients.…”
Section: Methodsmentioning
confidence: 99%